2021
DOI: 10.2174/1386207323666200712145041
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol-Drop Grinding Approach: Cadmium Oxide Nanoparticles Catalyzed the Synthesis of [1,3]Dioxolo[g][1]benzopyran-6-carboxylic Acids and Pyrido[d]pyrimidine-7-carboxylic Acids

Abstract: Aim and Objective: In the last decades, it has been extensively verified that nanostructured transition metal oxides emerge as inexpensive, available and extremely efficient heterogeneous catalysts in chemical transformations. The high electrical conductivity, high carrier concentration, and improved reactivity in cadmium oxide nanoparticles (CdO NPs) make it as a potential candidate for applications in the fields of nanocatalysis. [1]Benzopyran and pyridopyrimidine derivatives compose major classes of hetero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Recently, Dahi-Azar et al 78 reported an impressive procedure for the synthesis of 1,3-dimethyl-2,4-dioxo-5-phenyl-1,2,3,4,5,8-hexahydropyrido[2,3- d ]pyrimidine-7-carboxylic acids in 96–98% yields using a recyclable nanocatalyst. Thus, cyclocondensation reaction of 4-substituted phenylmethylidenepyruvic acids with 6-amino-1,3-dimethyluracil under ethanol drop grinding, and nano-catalytic conditions using cadmium oxide nanoparticles at room temperature.…”
Section: Synthesis Of Annulated Pyrido[23-d]pyrimidinesmentioning
confidence: 99%
“…Recently, Dahi-Azar et al 78 reported an impressive procedure for the synthesis of 1,3-dimethyl-2,4-dioxo-5-phenyl-1,2,3,4,5,8-hexahydropyrido[2,3- d ]pyrimidine-7-carboxylic acids in 96–98% yields using a recyclable nanocatalyst. Thus, cyclocondensation reaction of 4-substituted phenylmethylidenepyruvic acids with 6-amino-1,3-dimethyluracil under ethanol drop grinding, and nano-catalytic conditions using cadmium oxide nanoparticles at room temperature.…”
Section: Synthesis Of Annulated Pyrido[23-d]pyrimidinesmentioning
confidence: 99%